Calculation Of Ionization Rate Coefficients Of Helium-like Iron - Dilmi, S.; Guedda, E. H. (University of Eloued جامعة الوادي, 2012)
The atomic data of the various atomic processes are essential for the radiative collisional models describing the plasmas. In this work we present our computation results of the ionization rate coefficients of helium-like iron ions. These types of ions can exist in all the types of plasmas. We use a simple numerical method to generate the ionization rates starting from the cross sections which are obtained by FAC (Flexible Atomic Code). Our computation results will be compared with those publishe
Articale in Journal of fundamental and Applied Sciences Vol. 04 N. 01
Keywords: Atomic data, radiative collisional Models, Ionization rate, cross Sections of ionization.